Strategi Peningkatan Mutu Pendidikan Anak Yatim Melalui Genius Yatim Mandiri Di Desa Tanggungan Kecamatan Baureno - Suradji, Muchamad; Zulvia, Anik Ida (TADARUS, 2019)
AbstractThe purpose of this study is to explain the strategies for improving the quality ofeducation of orphans through independent orphan geniuses. The method used inthis study is qualitative. The collection techniques used are observation,documentation, and interviews. While data analysis uses stages, data reduction,triangulation, data display and verification. The results in this study can beemphasized on the strategy of improving the quality of education in building thefollowing characteristics: (a) improving the quality of education for orphans,especially in the fields of mathematics and other sciences. (b) guiding andassisting orphans who have the potential until they graduate and enter selection incollege. (c) printing orphans so that he is intelligent, polite and resilient (d) andfostering akhlaqul karimah in children. Keywords: Strategy, Quality Improvement, Education of Orphans, Genius,Independent Orphans